2013
DOI: 10.1080/14789949.2013.795238
|View full text |Cite
|
Sign up to set email alerts
|

Lived experiences of recalled mentally disordered offenders with dual diagnosis: a qualitative phenomenological study

Abstract: The lived experience of mentally disordered offenders with dual diagnosis was the focus of this study. Interviews with five recalled service users from a medium secure unit in England were subjected to an interpretative phenomenological analysis. Five themes were identified relating to identity, control, autonomy and recovery. Clinical implications include increasing service users' awareness of available post-diagnosis identities, which meet the needs of individuals' lived contexts and promotion of recovery-or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
(78 reference statements)
1
11
0
Order By: Relevance
“…Consequently, recovery in this population is described as 'dual' or 'secure' recovery. Taking a new identity may consist of giving the offence and its context a place in one's life and restoring the harm and guilt caused by it (O'Sullivan et al, 2013;Ferrito et al, 2012). Based on a meta-synthesis of five qualitative studies about personal recovery in forensic settings, Shepherd and colleagues (2016) identified the need for protection and security, the importance of hope and social support and taking a new identity as prerequisites for personal recovery.…”
Section: Mental Health Care: the Emerging Recovery Movementmentioning
confidence: 99%
“…Consequently, recovery in this population is described as 'dual' or 'secure' recovery. Taking a new identity may consist of giving the offence and its context a place in one's life and restoring the harm and guilt caused by it (O'Sullivan et al, 2013;Ferrito et al, 2012). Based on a meta-synthesis of five qualitative studies about personal recovery in forensic settings, Shepherd and colleagues (2016) identified the need for protection and security, the importance of hope and social support and taking a new identity as prerequisites for personal recovery.…”
Section: Mental Health Care: the Emerging Recovery Movementmentioning
confidence: 99%
“…Recovery for the offender patient (Drennan and Alred, ; Dorkins and Adshead, ) includes the notion of re‐establishing, or discovering, a post‐offending personhood after the impact of offending, through re‐gaining hope, control and opportunity and, critically, by placing the offender at the centre of his/her own care pathway. Personality disorder has introduced a series of specific challenges for forensic case formulators: possibly, the most important is working in genuine partnership with the offender/patient throughout the process, shifting the power balance in relation to the ownership of ‘expertise’ between patients and clinicians (Shepherd et al, ; O'Sullivan et al, ).…”
mentioning
confidence: 99%
“…Lack of sensational news in life can easily lead to negative feelings of unworthiness, boredom, frustration, and depression, which may negatively affect their recovery. As suggested by previous qualitative evidence that patients’ recovery in forensic hospitals may benefit from activities with employment prospects [21, 25, 26], we suggested that the hospitals should provide recovery-oriented programmes by increasing recreational activities, working opportunities and workshops on occupational and interpersonal skills.…”
Section: Discussionmentioning
confidence: 77%